Morphometry of the Splenium of the Corpus Callosum – A Study on 60 Cadaveric Brains (Bangladesh Journal of Neurosurgery, 2022)
Background: The splenium is the posterior most part of the corpus callosum; ageand sex-related differences in splenial morphology may influence some behavioural and neuropsychological functions; however, controversies still prevail on sexual dimorphism of the splenium.Objective: To provide data on morphology of the splenium of the corpus callosum in a Bangladeshi population.Materials and Methods: This crosssectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, Bangladesh, from July 2009 to June 2010, based on collection of 60 adult human brains (36 male and 24 female) from the morgue of the same institution. The samples were divided into four age groups: A (20-29 years), B (30-39 years), C (40-49 years) & D (50-59 years).The length and width of the splenium were measured in formalin-fixed brain by using a digital slide calipers in mm.Results: A total of 32 (52%) tubular shaped and 28 (47%) bulbous shaped splenium was found. Tubular shaped splenium was more observed in adult males, while bulbous shape was more evident in adult females; the difference was statistically significantinall age groups. The mean length of splenium was found 13.52±0.20 mm in group A, while 13.53±0.18 mm in group B, 13.46±0.05 mm in group C and 13.47±0.05 mm in group D (p>0.05). The mean length of the splenium was larger in male in comparison to female i.e. in group A (13.60±0.25 mm vs. 13.43±0.04 mm; p